2010
DOI: 10.3390/md8082318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ocean Acidification on Energy Metabolism of Oyster, Crassostrea gigas—Changes in Metabolic Pathways and Thermal Response

Abstract: Climate change with increasing temperature and ocean acidification (OA) poses risks for marine ecosystems. According to Pörtner and Farrell [1], synergistic effects of elevated temperature and CO2-induced OA on energy metabolism will narrow the thermal tolerance window of marine ectothermal animals. To test this hypothesis, we investigated the effect of an acute temperature rise on energy metabolism of the oyster, Crassostrea gigas chronically exposed to elevated CO2 levels (partial pressure of CO2 in the seaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
263
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(291 citation statements)
references
References 92 publications
22
263
4
2
Order By: Relevance
“…Similar results have been obtained for other calcifying organisms, e.g., the reduction in shell growth of the oysters Crassostrea gigas (Lannig et al, 2010) and Crassostrea virginica (Beniash et al, 2010), of the larvae of the Mediterranean pteropods Cavolinia inflexa (Comeau et al, 2010), and of the mussels Mytilus edulis (Gazeau et al, 2010) and Mytilus californianus (Gaylord et al, 2011). Along a gradient of pH (5.…”
Section: Comparison With Other Ocean Acidification Studiessupporting
confidence: 66%
“…Similar results have been obtained for other calcifying organisms, e.g., the reduction in shell growth of the oysters Crassostrea gigas (Lannig et al, 2010) and Crassostrea virginica (Beniash et al, 2010), of the larvae of the Mediterranean pteropods Cavolinia inflexa (Comeau et al, 2010), and of the mussels Mytilus edulis (Gazeau et al, 2010) and Mytilus californianus (Gaylord et al, 2011). Along a gradient of pH (5.…”
Section: Comparison With Other Ocean Acidification Studiessupporting
confidence: 66%
“…For example, OA was found to impact survival, development, physiology and growth of many marine mollusks [32]. Furthermore, OA exposure can also disturb the energy metabolism and regulation which might affect immune function in bivalves [14,18]. Recently, it has been found that OA stress has the potential to promote pathogen development and survival, disease transmission and host susceptibility [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OA stress has also been found to affect many physiological processes, such as calcification [13], energy metabolism [14] and behavior [15,16] of calcifying organisms. However, there is a lack of studies on the effects of OA on other vital processes of marine organisms such as immune and stress responses [17].…”
Section: Introductionmentioning
confidence: 99%
“…4) while four experiments concluded on an increase in their SMR during exposure to elevated CO 2 (Lannig et al 2010;Cummings et al 2011;Parker et al 2012), suggesting an ability to at least partially compensate for the increased energy costs of acidosis (Wicks and Roberts 2012). In the mussel M. edulis, for example, exposure to elevated CO 2 of 1,120 latm (-0.3 pH unit) for 60 days led to a significant increase in SMR .…”
Section: Other Physiological Processesmentioning
confidence: 99%